Hubungan Persepsi Kemudahan Penggunaan Aplikasi Jamsostek Mobile dengan Penggunaan Nyata pada Peserta BPJS Ketenagakerjaan Cabang Meulaboh - Irna Yanti; Maisyaroh Fitri Siregar; Safrizal Safrizal; Mardi Fadhilla; Perry Boy Chandra Siahaan (Universitas Pahlawan Tuanku Tambusai, 2026)
Advances in information technology have driven the digitization of public services, including at BPJS Ketenagakerjaan through the Jamsostek Mobile (JMO) app. This app aims to make it easier for participants to access social security services online. However, various obstacles remain, such as difficulties in using features, system disruptions, and low digital literacy, which can affect Actual Users’ ability to utilize the app. This study aims to analyze the relationship between the perceived ease of use (Perceived Ease of Use) of the JMO app and actual usage (Actual Usage) at the BPJS Ketenagakerjaan office in Meulaboh. The study employs a quantitative method with across-sectional design. The study population consists of 2,269 users. The study sample consisted of 96 respondents selected using simple random sampling based on the Slovin formula. Data were collected through questionnaires and interviews, then analyzed using chi-square tests. The results showed that the majority of respondents rated the JMO app as easy to use (91.7%). Furthermore, regarding actual usage, 93.8% of respondents reported good actual usage. This high percentage of actual usage indicates that the JMO app has been well-received by users and is utilized as a means to obtain information and access BPJS Ketenagakerjaan services. Theresults of the chi-square test indicate a significant relationship between the perceived ease of use and actual usage (p = 0.000). Therefore, improving the ease of access, navigation, and use of the app should be a top priority to increase the app’s actual usage in the future.